The Role of Non-State Actors in Climate Governance: Contributions, Challenges and Future Directions - Islam, Md Mujahidul; Jahan, Nusrat (Journal of Information System and Informatics, 2025)
Since anthropogenic causes accelerate rapid climate change with intensifying the adverse impacts of climate induce hazards, Non-State Actors (NSAs) have emerged as pivotal actors in climate governance. The aim of this research is to explore the diverse roles and contributions of NSAs in climate governance and analyze the challenges and institutional barriers they encounter with proposing some recommendations to strengthen their impact. It employs a qualitative approach where data were collected through KII method. Thematic analysis reveals some meaningful role of NSAs in climate governance including advocating for climate justice, raising awareness, promoting sustainable technologies, enhancing community adaptation and resilience, and collaborating across sectors. Digital awareness campaign of Greenpeace during the Copenhagen and Paris Conference and BRAC's climate-resilient housing and rainwater harvesting initiatives in Bangladesh can be placed as notable examples of NSAs’ roles. Despite their significant contributions, several persistent challenges such as poor coordination among NSAs and with state actors, legitimacy deficits, governance gaps, lack of institutional support and insufficient financing impedes them to realize their full potential. To overcome these challenges, this study recommends the need for legal inclusion of NSAs’ roles, inclusive participation, incorporating intersectionality, stronger accountability mechanisms and sustainable financial frameworks. Furthermore, this study offers actionable recommendations for policymakers and practitioners seeking to enhance the effectiveness of non-state engagement in climate action.